Effectiveness of a computerised system of patient education in clinical practice: a longitudinal nested cohort study. Issue 5 (3rd May 2018) - Su, Chia-Hsien; Li, Tsai-Chung; Cho, Der-Yang; Ma, Wei-Fen; Chang, Yu-Shan; Lee, Tsung-Han; Huang, Li-Chi
Abstract : Introduction: Developing electronic health record information systems is an international trend for promoting the integration of health information and enhancing the quality of medical services. Patient education is a frequent intervention in nursing care, and recording the amount and quality of patient education have become essential in the nursing record. The aims of this study are (1): to develop a high-quality Patient Education Assessment and Description Record System (PEADRS) in the electronic medical record (2); to examine the effectiveness of the PEADRS on documentation and nurses' satisfaction (3); to facilitate communication and cooperation between professionals. Methods and analysis: A quasi-experimental design and random sampling will be used. The participants are nurses who are involved in patient education by using traditional record or the PEADRS at a medical centre. A prospective longitudinal nested cohort study will be conducted to compare the effectiveness of the PEADRS, including (1): the length of nursing documentation (2); satisfaction with using the PEADRS; and (3) the benefit to professional cooperation. Ethics and dissemination: Patient privacy will be protected according to Electronic Medical Record Management Practices of the hospital. This study develops a patient education digital record system, which would profit the quality of clinical practice in health education. The results will be published in peer-reviewed journals and will be presented at scientific conferences.